Adsorption characteristics of a low-cost activated carbon for the reclamation of colored effluents containing malachite green - Sharma Y.C. (My University, 2025)
Adsorption characteristics of a low-cost activated carbon, rice husk activated carbon (RHAC), for the removal of malachite green (MG), a basic dye from aqueous solutions, have been investigated. Rice husk is peel-off from paddies and is a well-known agricultural waste material. Characterization of the activated carbon was carried out using different sophisticated methods. RHAC was characterized by Fourier transformation infrared spectrometry (FTIR), scanning electron microscopy (SEM), X-ray diffractometry (XRD), and thermogravimetric analysis (TGA). A nitrogen adsorption isotherm study revealed that the RHAC possessed micropores and mesopores. The porous properties of activated carbon were determined, and its surface area was found to be 180.50 m2/g. The RHAC was used for the removal of MG from its aqueous solutions. The effect of initial concentration and contact time, temperature, and pH on the removal of MG was investigated. The removal of MG decreased from (94.91 to 93.75) % by increasing the initial dye concentration from (60 to 100) mg/L. A study of the effect of temperature revealed the process of removal of dye to be endothermic. Kinetic studies of the process of adsorption were also carried out. The experimental data were used to study the Langmuir and Frendulich adsorption isotherms. © 2011 American Chemical Society.